Enacting Copywriting Skills during Distance Internship: A Case Study at IQR Foundation - Yessy Purnamasari; Tri Puji Nur Uzlifah (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2021)
Distance internship rises as global pandemic Covid-19 starts in the beginning of 2020. It forces the higher education institution to re-manage the rules of internship for second year students. As part of the regulation, the internship for Polban students was suggested to be done through distance methods. One of the NGOs that provide distance internships for English Department students is IQR Foundation. This study then investigates the enactment of students' copywriting skills and the challenges during distance internship. The data were collected by combining observation and study literature. The results show this distance internship enables students to apply copywriting skills through three enactments: composing script, creating English subtitles, and collaborating in news writing. Compared to the conventional one, distance internship leads to three main challenges: deciding concepts, using English as the language of communication, and handling the timeline. Distance internship, in many ways, has created many chances for students to grow up and to implement their knowledge in a new paradigm despite the pandemic as the boundary.